Penerapan Automation Testing dengan Cypress pada Website Klinik Healthcare Berbasis STLC Agile: Integrasi E2E dan Regression Testing - Ghaida Sandie Hayatus Sahla Sandie; Farhan Hamdallah; Muhamad Dzaky Ashidqi (JIKOMTI : Jurnal Ilmiah Ilmu Komputer dan Teknologi Informasi, 2026)
Advances in information technology have led to increased complexity in information systems for clinical services, particularly in patient data management, doctor scheduling, and healthcare transactions. This situation requires systems that are not only stable at initial release, but also remain reliable after feature updates. Therefore, software testing is necessary to ensure that each feature runs according to system requirements and does not interfere with existing functionality. This study applies automated testing using Cypress with an Agile-based Software Testing Life Cycle (STLC) approach, using end-to-end testing and regression testing methods. Testing was conducted on the clinic's website with the admin role as the main user who manages user authentication, master data, patient visits, and medication transactions. The test results showed that all test cases achieved a pass status after system improvements and adjustments were made. Thus, the implementation of Agile STLC-based automated testing is capable of supporting a structured, adaptive, and sustainable testing process in maintaining the quality of the clinic's information system.